PENGURANGAN KADAR MG2+ DAN MN2+ DALAM AIRMELALUI PEMANFAATAN ARANG AKTIF DAN BENTONITE - Maulani, Mustamina; Nugrahanti, Asri; Satiyawira, Bayu; Rosyidan, Cahaya; Samura, Lisa; Arkaan, Muhammad Dzaki; Michael, David; Nuryana, Suherman Dwi (Jurnal AKAL: Abdimas dan Kearifan Lokal, 2025)
Cikarawang Village, Dramaga, Bogor is a village with a large potential for water resources. However, the water in this village has high levels of Mg2+ and Mn2+. High levels of Mg2+ and Mn2+ can cause eye and nose irritation, as well as influenza symptoms. To reduce the levels of Mg2+ and Mn2+ in water, this study used the adsorption method using activated carbon and bentonite. The results of the study showed that the levels of Mg2+ and Mn2+ in water can be significantly reduced using the adsorption method. In sample 1, the level of Mg2+ decreased from 14.64% to 11.64% after adsorption for 30 minutes. In sample 2, the level of Mg2+ dropped to 0% after adsorption for 30 minutes. In sample 3, the level of Mg2+ decreased from 9.60% to 5.76% after adsorption for 30 minutes. In general, the longer the contact time between the sample and the adsorbent, the greater the decrease in the levels of Mg2+ and Mn2+. However, for sample 2, the level of Mg2+ dropped to 0% after adsorption for 30 minutes. This indicates that sample 2 has a very high level of Mg2+ that can be adsorbed perfectly by bentonite in a short time. This study concluded that the adsorption method using activated carbon and bentonite is an effective method for reducing the levels of Mg2+ and Mn2+ in water.